Sistemas de terminação e pesos de abate de bovinos leiteiros visando à produção de carne de vitelão - Santos, Priscila Vincenzi dos (2013)
The work was developed at Federal Technological University of Paraná, Campus Two Neighbors, with the objective of evaluating the characteristics and physical carcass composition and meat Holstein calves finished on pasture with supplementation or confinement and slaughtered at different weights. We used 43 animals, Holstein, with an initial weight of 57 kg at weaning and 58 days old, divided into two finishing systems and slaughter weights in four pre-stipulated: 140, 180, 220 and 260 kg of body weight . Twenty-three animals were housed individually fed a diet consisting of corn silage as forage and concentrate commercial about 40:60. The twenty remaining animals were terminated on oat (Avena sativa) intercropped with ryegrass (Lolium multiflorium), African Star (Cynodon nlemfuensis) and millet (Pennisetum glaucum) and received daily supplementation with concentrated even 1% of body weight . The feedlot finishing enabled reduction of slaughter age compared to pasture, providing greater fat cover and better carcass conformation, however, carcass yield was similar between finishing systems. Carcass traits improved with increasing slaughter weight. Animals finished on pasture had a higher percentage of muscle, lower percentage and amount of fat in relation to animal confinement. As slaughter weight increased there was an increase in the total amount of muscle, bone and fat, muscle / bone ratio and ratio edible portion / bone, palatability and juiciness for both systems. The percentage of bone and flesh color decreased with increasing slaughter weight. The animals finished on pasture had better meat texture with increasing slaughter weight.